Journey into virtual reality: Identifying behavioral intentions to use virtual reality in tourism through spectral clustering - Attasit Wiangkham; Komsit Kieanwatana; Rattawut Vongvit (Journal of Open Innovation: Technology, Market and Complexity)
Virtual Reality (VR) holds immense potential to revolutionize the tourism industry by transforming how destinations are marketed and experienced. Research consistently emphasizes VR’s ability to enhance and enrich tourist experiences, offering new dimensions of engagement. However, despite its promise, concerns about diminished motivation to interact with VR-enabled attractions may hinder widespread adoption. This study, through the application of Exploratory Factor Analysis and spectral clustering of empirical survey data, aims to identify clusters of behavioral intentions for using VR in tourism based on an extended Technology Acceptance Model (TAM). These clusters, namely Cluster A (''Cautious Travelers''), Cluster B (''Disenchanted Travelers''), Cluster C (''Quality-Seeking Travelers''), and Cluster D (''Information-Driven Travelers''), highlight the critical role of comprehensive destination knowledge and the importance of information access in enhancing the VR tourism experience. By understanding the behaviors and preferences of these groups, businesses and developers can create tailored VR content and experiences that improve user satisfaction with a focus on ease of use and content quality.